Complication Rates of Catheter Ablation of Atrial Fibrillation in Patients Aged ≥75 Years versus <75 Years—Results from the German Ablation Registry. (14th January 2017) - MOSER, JULIA M.; WILLEMS, STEPHAN; ANDRESEN, DIETRICH; BRACHMANN, JOHANNES; ECKARDT, LARS; HOFFMANN, ELLEN; KUCK, KARL‐HEINZ; LEWALTER, THORSTEN; SCHUMACHER, BURGHARD; SPITZER, STEFAN G.; HOCHADEL, MATTHIAS; SENGES, JOCHEN; et al.
Age‐Related Complication Rates in AF Ablation: Introduction: Despite a rising demand for catheter ablation (CA) of atrial fibrillation (AF) in an elderly population, complication and success rates are not fully elucidated. We sought to compare complication rates of CA of AF in patients ≥75 versus <75 years of age. Methods and Results: Patients with symptomatic, drug‐refractory AF were prospectively enrolled from January 2007 to 2010 in this multicenter study. A total of 4, 449 patients, group 1 ≥75 years and group 2 <75 years (n = 227, age 77.3 ± 2.2 vs. 59.7 ± 9.8 years, 52.0% vs. n = 4, 222, 68.9% male, CHA2 DS2 ‐VASc‐Score 3.7 ± 1.0 vs. 1.7 ± 1.2; P < 0.001, respectively), with paroxysmal AF (59.9% in group 1 vs. 63.3% in group 2, P = 0.30), and persistent AF (34.8% in group 1 vs. 29.4% in group 2, P = 0.082) underwent CA of AF. A centralized follow‐up was obtained in 4, 347 patients by the Institute for Myocardial Infarction Research (IHF, Ludwigshafen). There was a significant difference between periprocedural stroke rates in the elderly versus the younger cohort (1.3% vs. 0.1%, P < 0.01). In‐hospital severe nonfatal complications did not differ significantly between the groups (4.4% vs. 2.7%, P = 0.14). Other procedure‐related, in‐hospital complications were not significantly different. After a mean follow‐up of 472 ± 99 days (group 1) and 477 ± 94 days (group 2), no differences were found in complication rates. Conclusion: CA of AF in patients ≥75 years is associated with higher in‐hospital stroke rates. In a 1‐year follow‐up, complication rates do not differ between the groups.